Midwife Care In Ny.R Family Planning With Implant Method In Mandiri Midwife Practice Sri Kurniawati - Tri Suci Dewi Wati; Indah Wahyuni (Institute of Computer Science (IOCS), 2021)
Efforts are being made to control the population and direct the mobility of the population to create a society that grows in balance with the family planning program (KB). A quality and prosperous small family can be planned by every family through the family planning program. Providing family planning midwifery care to Mrs. Implant acceptor using Varney's 7-step obstetric management. The case study used a descriptive method with the scope of patients being Kb implant acceptors, when it was carried out on June 3, 2021 to June 7, 2021 at PMB Sri Kurniawati according to midwifery science. On June 3, 2021 to June 7, 2021 Mrs. R has become an implant KB acceptor, the implant is installed well and the mother has received therapy. Family planning care is done by providing counseling to mothers about the contraceptives used so that Mrs. Rahayu decided to become a new acceptor of KB implants by signing the infoconsent that had been given to the mother for implant placement. After post-implant installation, the mother received KIE regarding post-implant family planning treatment.